Business Training for New and Existing Female-Owned Firms in Sri Lanka - de Mel, Suresh; McKenzie, David; Woodruff, Christopher (World Bank, Washington, DC, 2014)
This note discusses one of a number of recent impact evaluations of business training programs. Further reading provides a link to a critical overview of this new literature.